Employing AI Technologies in News Notifications for Electronic Platforms: Field Study on Communicators in Iraqi News Websites from 1/4/2024 to 30/4/2024 - Azziz, Semaa Sadoon (Dirasat: Human and Social Sciences, 2025)
Objectives: The research aims to understand the attitudes of communicators in Iraqi news websites towards the employment of artificial intelligence (AI) technologies in sending news notifications and the extent to which media institutions can utilize these technologies in terms of financial, software, and skill capabilities. Methods: The survey method, a type of descriptive research, was used by collecting data through the distribution of an electronic questionnaire using a snowball sample of 45 workers in Iraqi media websites within the study period. Results: The study revealed that AI technologies are not employed in Iraqi media institutions, particularly in news websites and the sending of news notifications, despite these websites having the financial and technical capabilities to employ this technology in the notification service. This is due to a lack of awareness among communicators about the importance of employing this technology in media content production, as well as weak infrastructure caused by digital illiteracy and the limited participation in Arab and foreign training courses related to the production and creation of media content using AI technologies according to the legal and ethical constraints that align with social customs and traditions which help in the adoption of media content by the audience. Conclusion: The study concluded, based on the opinions of workers in news websites, the importance of employing AI technologies in the field of sending notifications on news websites due to its role in enhancing the media message with more accuracy and professionalism and the prior knowledge of the tendencies and desires of the target audience across different categories, increasing speed, contemporaneity, and rapid coverage of important news events.